CRITERIA FOR MAKING A DECISION ON THE SELECTION OF SWIMMING POOLS DEPENDING ON THE LEVEL OF KNOWLEDGE ABOUT THE BLUE FLAG IN MONTENEGRO - Šljivančanin, Svetlana (The Business of Tourism, 2020)
Swimming areas in Montenegro represent a generator of development of the tourist economy. Their arrangement and equipment was done in accordance with the legislation. International standards are not applied in business, but one part of the beach has a prestigious international award "Blue Flag", which guarantees quality service and environmental protection at a high level. Swimming guests have different criteria for choosing the beach where they will rest and their choice does not depend only on subjective affinities, but also on the quality offer and knowledge of the blue flag.